Työhyvinvointi liikunnanopettajan työssä – Laadullinen tutkimus työhyvinvoinnin merkityksestä, siihen vaikuttavista tekijöistä sekä edistämisen keinoista - Laitinen, Julia; Töyry, Mika-Matti (2025)
Laitinen, J & Töyry, M-M. 2025. Physical education teachers’ wellbeing at work – a qualitative study on its meaning, influencing factors, and ways to promote it. Faculty of Sport and Health Sciences, University of Jyväskylä, Master’s thesis in sport pedagogy, 79 pp.. 1 appendix.